ANALISIS SUB SEKTOR UNGGULAN YANG BERDAYA SAING PADA SEKTOR PERTANIAN DI KABUPATEN LANGKAT - Harahap, Muhammad Rif’an (TABULARASA, 2014)
System changes from centralized to decentralized governance has provided an opportunity for local governments to regulate and manage Natural Resources (NR) and Human Resources (HR) in the region to create a welfare society can be characterized by the growth of regional economic growth. The research was conducted to determine the contribution and sub-sectors growth in the agricultural sector and a base and competitive sub-sectors so that it can be seen the leading subsectors of agriculture. The analysis method used is descriptive analysis will illustrate how the rate of growth and the contribution of sub-sectors in the agricultural sector. Location Quetiont (LQ) Analysis was used to determine the base and non-base sub-sector. While the analysis of Revealed Comparative Advantage (RCA) is used to see the sub-sector competitiveness. The combination of LQ and RCA analysis can then be used to determine the leading sub-sector. From the analysis it is known that sub-sector of the agricultural sector is a base sub-sector which has the potential to become the leading sub-sector. Meanwhile, from the RCA analysis is known that the base of the agricultural sector has a highly competitive sub-sectors are food crops, tree crops, livestock and forestry.